2014
DOI: 10.1007/s10646-014-1235-5
|View full text |Cite
|
Sign up to set email alerts
|

Experimental manipulation of dietary lead levels in great tit nestlings: limited effects on growth, physiology and survival

Abstract: We manipulated dietary lead (Pb) levels of nestlings in wild populations of the great tit (Parus major L) to find out if environmentally relevant Pb levels would affect some physiological biomarkers (haematocrit [HT], fecal corticosterone metabolites [CORT], heat shock proteins [HSPs], erythrocyte delta-aminolevulinic acid dehydratase activity [ALAd]), growth (body mass, wing length), phenotype (plumage coloration) or survival of nestlings. The responses to three experimental manipulation (control, low and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 85 publications
6
34
1
Order By: Relevance
“…However, to cause severe long-lasting effects on cognition, developmental levels of Pb may have to be relatively high and acutely toxic. In our case, the nestlings in the Pb treatment did not show symptoms of acute toxicity: in a companion paper from the same study setup (Eeva et al 2014), we report that growth (body mass) was not impaired compared with the controls in our study (wing growth tended to even increase with low Pb exposure). Also, physiological biomarkers (hematocrite, fecal corticosterone, with the exception of HSP60) and especially a Pb-specific marker, Ala-D enzyme activity were not affected by Pb treatment in our study (results reported in Eeva et al 2014), suggesting that exposure levels were too low to cause acute toxicity.…”
Section: Lead Exposuresupporting
confidence: 59%
See 3 more Smart Citations
“…However, to cause severe long-lasting effects on cognition, developmental levels of Pb may have to be relatively high and acutely toxic. In our case, the nestlings in the Pb treatment did not show symptoms of acute toxicity: in a companion paper from the same study setup (Eeva et al 2014), we report that growth (body mass) was not impaired compared with the controls in our study (wing growth tended to even increase with low Pb exposure). Also, physiological biomarkers (hematocrite, fecal corticosterone, with the exception of HSP60) and especially a Pb-specific marker, Ala-D enzyme activity were not affected by Pb treatment in our study (results reported in Eeva et al 2014), suggesting that exposure levels were too low to cause acute toxicity.…”
Section: Lead Exposuresupporting
confidence: 59%
“…On d7 and 14, chicks were measured (wing length and body mass). We ringed and collected a blood sample for molecular sexing (see details in Eeva et al 2014) and a fecal sample for noninvasive analyses of Pb levels on d7.…”
Section: General Experimental Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…Heavy metal pollution may pose both direct and indirect detrimental effects on birds' reproductive success. To assess their relative importance, a recent study (Eeva et al 2014) manipulated the dietary lead (Pb) levels at Great Tit Parus major nests, and compared these nestlings' physiological, biometrical and plumage traits to those of the nestlings living in a heavily polluted area (near a copper smelter). Despite of the similar exposure of lead in the treatment group and in the birds of the highly polluted area, chicks of the latter exhibited lower survival, decreased size and also the signs of inferior health state, compared to the treatment groups.…”
Section: Habitat Urbanization and Its Effects On Birdsmentioning
confidence: 99%